Separation of bacteria Kocuria rhizophila BR-1 from its broth during synthesis of gold nanoparticles using ceramic membrane by shear-enhanced filtration process. (October 2021) - Dahiya, Digvijay; Pugazhenthi, G.; Kumar, Mohit; Vasanth, D.
Abstract: In the present study, disc type ceramic membranes made from China clay, quartz and calcium carbonate were used for the separation of bacteria Kocuria rhizophila from its broth by shear-enhanced filtration process. Porosity, water permeability and average pore size of the membrane were 42%, 3.24 × 10 −4  L m −2 h −1 Pa −1 and 180 nm, respectively. The membrane exhibited good chemical tolerance in acid, alkali and chlorine solutions. The effect of trans -membrane pressure and rotational speed on permeate flux and bacterial rejection was investigated. It was found that the permeate flux increased (40–163.5 L m −2 h −1 ) and bacterial rejection decreased (99.2–94.5%) with increasing pressure (69–345 kPa). With an increase in rotation (50–250 rpm), the permeate flux increased from 156.5 to 176.8 L m −2 h −1, while bacterial rejection decreased from 94.3 to 83.2%. The pressure of 345 kPa and rotational speed of 250 rpm with flux of 176.8 L m −2 h −1 and rejection of 83% was selected as an optimum process condition. The analysis of fouling models revealed that the cake filtration model provided the highest R 2 (0.89) value followed by intermediate pore blocking (0.87) which indicates that cake filtration model has the best fit with the experimental data. Henceforth, the shear enhanced filtration process used in this study can be considered as a pertinent filtration process for efficient recovery of biological products at industrial scale. Graphical abstract: Image 1 Highlights: Shear enhanced filtration setup was fabricated to reduce the fouling of membrane. Ceramic membranes were fabricated from naturally available low cost clay materials. Gold nanoparticles producing bacteria Kocuria rhizophila was successfully recovered. The membrane showed 83% of bacterial rejection with permeate flux of 176.8 L m −2 h −1 . Shear enhanced filtration process showed significant reduction in membrane fouling.